2016
DOI: 10.4132/jptm.2016.03.29
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Tumor Multifocality Is Important for Prediction of Tumor Recurrence in Papillary Thyroid Microcarcinoma: A Retrospective Study and Meta-Analysis

Abstract: Background:The clinicopathological characteristics and conclusive treatment modality for multifocal papillary thyroid microcarcinoma (mPTMC) have not been fully established.Methods:A retrospective study, systematic review, and meta-analysis were conducted to elucidate the clinicopathological significance of mPTMC. We investigated the multiplicity of 383 classical papillary thyroid microcarcinomas (PTMCs) and the clinicopathological significance of incidental mPTMCs. Correlation between tumor recurrence and mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 32 publications
(38 reference statements)
4
12
0
4
Order By: Relevance
“…Most patients with PTMC demonstrated excellent clinical outcomes, and all PTMC patients with recurrences could reach a disease-free state after re-operation. These findings are consistent with previous studies (5,6,7,8,10,11,12). In multivariate analyses, younger age, male gender, multifocality and cervical LN metastasis were related to recurrence of PTMC, as previously reported (5,6,9,10,11,12,13,14).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Most patients with PTMC demonstrated excellent clinical outcomes, and all PTMC patients with recurrences could reach a disease-free state after re-operation. These findings are consistent with previous studies (5,6,7,8,10,11,12). In multivariate analyses, younger age, male gender, multifocality and cervical LN metastasis were related to recurrence of PTMC, as previously reported (5,6,9,10,11,12,13,14).…”
Section: Discussionsupporting
confidence: 93%
“…Disease-specific mortality rate of patients with PTMC who underwent treatment is less than 1%, loco-regional recurrence rate is 2-4% and distant recurrence rate is 1-2% (5,6,7,8). The prognostic factors for recurrence in patients with PTMC were known such as age, large primary tumor size (>0.5 cm), presence of extrathyroidal extension, multifocal tumor and the presence of cervical lymph node (LN) metastasis (5,6,9,10,11,12,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…There was a difference statically significant between group A and group B in terms of neck hematoma (0.5% vs 3.7%), temporary hypoparathyroidism (11.4% vs 21.4%) and temporary unilateral nerve injury (1.5% vs 6.4%). According to Literature data, the recurrence rate in central lymph nodes compartment in patients aged over 65 years was higher compared to series of younger patients and was associated with a higher tumor staging and an increased rate of tumor multifocality [ 5 , 43 , 44 ]. Considering the patient stratified by age, the Authors reported a double rate of central lymph nodes compartment recurrence in over 75 years old patients, without statistically significant difference with patients aged 65–74 years.…”
Section: Discussionmentioning
confidence: 99%
“…Hong et al [25] confirmed that PTMC with age≤45, irregular morphology, and microcalcification was more likely to have CLNM. Pyo et al [37] found that multifocality in PTMC was significantly associated with aggressive behavior of the tumor. Jeon et al [38] found that male patients <50 years of age, tumors located in the upper or subcapsular, and microcalcification had a higher risk of LLNM (Fig.…”
Section: Correlation Between Lymph Node Metastasis Of Ptmc Ultrasonomentioning
confidence: 99%